Oral History Program Interview: Robert Lewis Kessler Jr. - Kessler, Robert Lewis Jr.
Kessler was born in Guthrie, Logan County, Oklahoma in 1921. He came out to Bakersfield, California in 1934 with his family. In this interview, Kessler describes experiencing other races of people other than white, moving to different locations in California, how kids bullied Kessler for being poor and having an accent, the effects of the WPA program, and the border inspection.